During or prenatal guidance on ordering colostrum for diabetic patients means: Integrative review (Research, Society and Development, 2023)
Objective: to identify in the literature which evidences of pregnant women with gestational diabetes received guidance for offering colostrum in the first hours of the newborn's life. Method: integrative literature review. The survey of studies was carried out by the Virtual Health Library, in March 2023, in the LILACS and MedLine databases. The search, selection and analysis of articles were carried out by two independent examiners and in case of disagreements, a third examiner was invited to participate in the consensus meeting on the selection of studies. After recurrent readings, the articles that made up the final sample were organized in a Microsoft Office Excel® spreadsheet. Results: There were no significant differences in rates of hypoglycemia; Babies born to pumping mothers were significantly less likely to receive formula in the hospital; early contact with cow's milk protein may increase the risk of type 1 diabetes; Uninterrupted skin-to-skin contact between mother and baby increases brown adipose tissue metabolism and the occurrence of gluconeogenesis and ketogenesis that decrease the likelihood of hypoglycemia. Conclusion: prenatal guidance and teaching to perform milking during pregnancy is beneficial, both for the mother who acquires familiarity with her body, along with stimulation of lactation as well as benefits for the NB. The practice considerably minimizes the use of formula, which reduces future complications and illnesses for the child.